Analysis of Various Approaches to Modeling of Dynamics of Lifting-Transport Vehicles - Grigorov, Otto; Druzhynin, Evgenij; Anishchenko, Galina; Strizhak, Marjana; Strizhak, Vsevolod (International Journal of Engineering and Technology, 2018)
The results of analytical and numerical modeling of dynamic characteristics of linear and non-linear mathematical models of the â€œtrolley-loadâ€ system of bridge and container cranes are presented. KiDyM software complex is used for numerical modeling, which, based on the use of the apparatus of structural matrices and the built-in computer algebra system, allows the construction of ordinary differential equations of motion of the class of systems under consideration at the analytical level. Recommendations on the possible use of the considered mathematical models of the â€œtrolley-loadâ€ system in various regular and forced operation modes of bridge and container cranes are given on the basis of the analysis. The ratio of the results of calculations for various design models of regular and forced operation of the bridge crane has been established. The magnitude of the distribution of the maximum values of the dynamic characteristics of motion of the container crane has been designed by calculating the forced operation mode using various mathematical models.Â Â